Screening for Analgesic and Anti-Inflammatory Effect of Antioxidants by Applying Formalin Test Using Albino Mice - Aburawi S*, Al Tubuly R, Friwan A, Al-Ghdamsi M (AlQalam Journal of Medical and Applied Sciences, 2017)
Objective: Aim of this work is to evaluate analgesic and anti-inflammatory effects of antioxidants. Methods: Formalin test was applied using albino mice. This model constitutes two distinct phases: the first phase represents the irritating effect of formalin at the sensorial fiber-C, while the second phase is inflammatory pain response. Results: Vitamin C, vitamin E and selenium have analgesic effect for neuropathic pain. Vitamin E and selenium produce anti-inflammatory effect.Conclusion: Analgesic effect for neuropathic pain was observed with vitamin C, vitamin E and selenium treatment. Anti-inflammatory effect is produced by vitamin E and selenium administration; while Vitamin C produces insignificant decrease in inflammation in the dose used.